2011
DOI: 10.1123/pes.23.4.600
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Fundamental Movement Skill Development and Physical Activity in Early Childhood Settings: A Cluster Randomized Controlled Trial

Abstract: The aim of this study was to assess the feasibility, acceptability and potential efficacy of a physical activity program for preschool children. A 20-week, 2-arm parallel cluster randomized controlled pilot trial was conducted. The intervention comprised structured activities for children and professional development for staff. The control group participated in usual care activities, which included designated inside and outside playtime. Primary outcomes were movement skill development and objectively measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
239
1
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(264 citation statements)
references
References 34 publications
8
239
1
16
Order By: Relevance
“…Accordingly, studies showed that goal directed approaches for developing FMS result in significant improvements in performance (Jones et al, 2011;Logan, Robinson, Wilson, & Lucas, 2012;McKenzie, Alcaraz, Sallis, & Faucette, 1998). Two Australian projects serve as examples: "Move it groove it" and "Get skilled get active".…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, studies showed that goal directed approaches for developing FMS result in significant improvements in performance (Jones et al, 2011;Logan, Robinson, Wilson, & Lucas, 2012;McKenzie, Alcaraz, Sallis, & Faucette, 1998). Two Australian projects serve as examples: "Move it groove it" and "Get skilled get active".…”
Section: Resultsmentioning
confidence: 99%
“…Physical activity programs have been proven feasible and potentially efficacious in preschool children (21). Our detailed data could improve the timing of indoor and outdoor activity facilities and interventions at the times of year when levels of physical activity are low.…”
Section: Physical Activity During the Yearmentioning
confidence: 96%
“…We have good available evidence-based programs targetting FMS development that are efficacious, translatable and scalable for the early childhood sector to integrate. Examples include Tooty Fruity Vegie in Preschools, 21,22 found to have long-term beneficial outcomes 23,24 and translated successfully across NSW as Munch and Move 25 and also Jump Start, 26 currently being translated in childcare settings in Tasmania.…”
mentioning
confidence: 99%